A SkyMapper view of the Large Magellanic Cloud: the dynamics of stellar populations. Issue 1 (12th December 2019) - Wan, Zhen; Guglielmo, Magda; Lewis, Geraint F; Mackey, Dougal; Ibata, Rodrigo A
ABSTRACT: We present the first SkyMapper stellar population analysis of the Large Magellanic Cloud (hereafter LMC), including the identification of 3578 candidate Carbon Stars through their extremely red g − r colours. Coupled with Gaia astrometry, we analyse the distribution and kinematics of this Carbon Star population, finding the LMC to be centred at (RA, Dec.) = (80.90° ± 0.29, −68.74° ± 0.12), with a bulk proper motion of (μ _α , μ _δ ) = (1.878± 0.007, 0.293± 0.018) mas yr^-1 and a disc inclination of i = 25.6° ± 1.1 at position angle θ = 135.6° ± 3.3°. We complement this study with the identification and analysis of additional stellar populations, finding that the dynamical centre for red giant branch stars is similar to that seen for the Carbon Stars, whereas for young stars the dynamical centre is significantly offset from the older populations. This potentially indicates that the young stars were formed as a consequence of a strong tidal interaction, probably with the Small Magellanic Cloud. In terms of internal dynamics, the tangential velocity profile increases linearly within \!3 kpc, after which it maintains an approximately constant value of V_ rot = 83.6± 1.7 km s^-1 until \!7 kpc . With an asymmetric drift correction, we estimate the mass within 7 kpc to be M_LMC(7 kpc) = (2.5± 0.1)× 10^10M_ and within the tidal radius (\! 30 kpc ) to be M_LMC(30 kpc) = (1.06 ± 0.32)× 10^11 M_, consistent with other recent measurements.